Crosstalk between TLR8 and RIG-I-like receptors enhances antiviral immune responses - Killian E. Vlaming; Killian E. Vlaming; Kelly van Wijnbergen; Kelly van Wijnbergen; Tanja M. Kaptein; Tanja M. Kaptein; Monique Nijhuis; Neeltje J. Kootstra; Neeltje J. Kootstra; Godelieve J. de Bree; Teunis B. Geijtenbeek; Teunis B. Geijtenbeek (Frontiers in Medicine, 2023)
BackgroundToll-like receptor (TLR) agonists have been investigated due to their potential dual effects as latency reverting agents and immune modulatory compounds in people living with HIV (PLWH). Here, we investigated whether co-stimulation of TLR7/8 agonists with RIG-I-like receptor (RLR) agonists enhances antiviral immunity.MethodsPeripheral blood mononuclear cells (PBMCs) and monocyte-derived dendritic cells (DCs) were incubated with TLR and RLR-agonists for 24 h and innate and adaptive immune responses were determined (maturation markers, cytokines in supernatant, ISG expression).ResultsBoth TLR7 and TLR8 agonists induced pro-inflammatory cytokines in DCs as well as PBMCs. TLR8 agonists were more potent in inducing cytokine responses and had a stronger effect on DC-induced immunity. Notably, while all compounds induced IL-12p70, co-stimulation with TLR8 agonists and RLR agonist polyI: C induced significantly higher levels of IL-12p70 in PBMCs. Moreover, crosstalk between TLR8 and RLR agonists induced a strong type I Interferon (IFN) response as different antiviral IFN-stimulated genes were upregulated by the combination compared to the agonists alone.ConclusionOur data strongly suggest that TLR crosstalk with RLRs leads to strong antiviral immunity as shown by induction of IL-12 and type I IFN responses in contrast to TLRs alone. Thus, co-stimulation of TLRs and RLRs might be a powerful strategy to induce reactivation of latent reservoir as well as antiviral immunity that eliminates the reactivated cells.